Social Criticism as a Factor of Collective Action (Social and Philosophical Approach) - Boichenko, Mykhailo; Polishchuk, Olexander; Horokhova, Iryna (Studia Warmińskie, 2018)
The article is devoted to the phenomenon of social criticism (theoretical search for a possible social order) as a potential for collective action in various social contexts. The authors analyze the impact of social criticism on the change of language used and the behavior of members of civil society. They emphasize that Realpolitik (or a policy based on the calculation of strength and interests of specific social entities) does not seem to be testing anymore when it comes to ensuring further sustainable and peaceful development of humanity. They also note that an interesting alternative to Realpolitik is social criticism, because it indicates directions and reveals the possibilities of realizing certain values within the social order. The social processes presented in the article are analyzed in the context of the so-called Ukrainian revolution of dignity. The authors point out that the events that took place in Ukraine at the turn of 2013 and 2014 were a collective manifestation in the hope of a new, changed social order in the country. The revolution of dignity has contributed to the change in the language used, the symbolism of statehood and the behavior of Ukrainian society.